Performance Evaluation of the Ionospheric Models AfriTEC and NeQuick 2 at the BF01 Station in Ouagadougou Between 2013 and 2021 - Karim Guibula; Pouraogo Ouédraogo; Salfo Kaboré; Frédéric Ouattara; Rolland Fleury (International Journal of Geophysics, 2025)
This manuscript examines the performance of two ionospheric models, AfriTEC and NeQuick 2, at station BF01 (lat. 12.3714° N, long. −1.5197° W) in Ouagadougou, Burkina Faso, situated in the West African equatorial region. The study is aimed at aiding in selecting an appropriate ionospheric model for this region, where in situ data are scarce. It involves comparing the VTEC values derived from RINEX files obtained at station BF01 with those provided by the two models, AfriTEC and NeQuick 2. Two periods were distinguished: a period of high solar activity (Rz≥50) between 2013 and 2015 and a period of low solar activity (Rz<50) from 2016 to 2021. The results show that during periods of high solar activity, both models underestimate VTEC with relative differences of up to −60%. However, AfriTEC is closer to the RINEX values during hours of strong sunlight. Between 2016 and 2021, the performance of the models gradually improves, with AfriTEC being more stable and more consistent with the RINEX data, especially during periods of VTEC peak. NeQuick2 performs less well during hours of strong sunshine and at night, with greater deviations from the RINEX data. From this study, it emerges that AfriTEC is the most suitable ionospheric model for predicting VTEC at station BF01.